PENGARUH PENURUNAN KADAR VASCULAR ENDOTHELIAL GROWTH FACTOR-A (VEGF-A) TERHADAP KEJADIAN ODEM OTAK PADA PASIEN STROKE ISKEMIK AKUT - , Ismail Setyopranoto, dr., Sp.S, Prof. Dr. dr. Samekto Wibowo, P.Far.K., Sp.FK.(K)., Sp.S(K). ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Hypoxia that occurs in ischemic stroke will trigger the proliferation of smooth muscle cells and endothelial cells to form new blood vessels. Due to hypoxia is the transcription of genes would be controlled by HIF-1, HIF-1 then activates genes responsible for angiogenesis is VEGF. VEGF may affect vascular permeability and lead to blood brain barrier leakage, causing brain edema. Cytokines in stroke play on the mechanisms of plaque rupture and atherogenesis. Cytokines will lead to decrease production of VEGF. Brain edema can lead to progressive neurological deterioration. The purpose of this study is proving that the decreased levels of VEGF-A contribute to the incidence of brain edema in acute ischemic stroke patients. This is a prospective observational analytic study using the case-control design in acute ischemic stroke patients treated in Stroke Unit Dr Sardjito General Hospital Yogyakarta. Comparative analysis performed on brain edema group and non brain edema group as well as the comparison of levels of VEGF-A in both. To find potentially significant independent factor on the role of VEGF-A in the incidence of brain edema, logistic regression analysis was performed. The significance level used was 0.05 or level of confidence 95% (p<0.05), with power test 50%. There are 71 subjects, consist of 37 subjects as a brain edema group, and 34 subjects as non brain edema group. The mean levels of VEGF-A on brain edema group is 436 pg/ml, and in non brain edema group is 746 pg/ml, this difference is statistically significant (95%CI: 5.5-615, p=0.046). The proportion of VEGF-A levels <638.3 pg/ml in brain edema group is greater than non brain edema (83.78% vs. 58.82%), this difference is statistically significant (OR=3.6